The (un)expected in describing and understanding sociolinguistic complexity in translingual practices of deaf students - Nogueira, Aryane S. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
This article presents a translingual and multimodal analysis of an interaction between deaf students attending a Portuguese course in order to reflect about the unexpected use of resources in the event in question. For this purpose, a set of ethnographic recordings was used to describe and analyze the interaction event in relation to the different contextual materials and normativity centers orienting the participants’ actions. The analyzed event revealed different scales in conflict in which the complexity and unpredictability of linguistic functioning referred to the multi-layered aspects of the language that were mobilized and, at the same time, to the field of language ideologies. Thus, the (un)expected, when explained, proved to be a crucial key to describing and constructing a more comprehensive understanding of how language actually works in the classroom with deaf students, with implications for research on deafness affiliated to the applied field of language studies and for teacher training.